Prediction of pre‐eclampsia in twin pregnancy by maternal factors and biomarkers at 11–13 weeks' gestation: data from EVENTS trial. (1st February 2021) - Benkő, Z.; Wright, A.; Rehal, A.; Cimpoca, B.; Syngelaki, A.; Delgado, J. L.; Tsokaki, T.; De Alvarado, M.; Vojtassakova, D.; Malligiannis Ntalianis, K.; Chaveeva, P.; Del Campo, A.; et al.
ABSTRACT: Objectives: First, to validate a previously developed model for screening for pre‐eclampsia (PE) by maternal characteristics and medical history in twin pregnancies; second, to compare the distributions of mean arterial pressure (MAP), uterine artery pulsatility index (UtA‐PI), serum placental growth factor (PlGF) and serum pregnancy‐associated plasma protein‐A (PAPP‐A) in twin pregnancies that delivered with PE to those in singleton pregnancies and to develop new models based on these results; and, third, to examine the predictive performance of these models in screening for PE with delivery at < 32 and < 37 weeks' gestation. Methods: Two datasets of prospective non‐intervention multicenter screening studies for PE in twin pregnancies at 11 + 0 to 13 + 6 weeks' gestation were used. The first dataset was from the EVENTS (Early vaginal progesterone for the preVention of spontaneous prEterm birth iN TwinS) trial and the second was from a previously reported study that examined the distributions of biomarkers in twin pregnancies. Maternal demographic characteristics and medical history from the EVENTS‐trial dataset were used to assess the validity of risks from our previously developed model. The combined data from the first and second datasets were used to compare the distributional properties of log10 multiples of the median (MoM) values of UtA‐PI, MAP, PlGF and PAPP‐A in twin pregnancies that delivered with PE to those in singleton pregnancies and develop new models based on these results. The competing‐risks model was used to estimate the individual patient‐specific risks of delivery with PE at < 32 and < 37 weeks' gestation. Screening performance was measured by detection rates (DR) and areas under the receiver‐operating‐characteristics curve. RESULTS: The EVENTS‐trial dataset comprised 1798 pregnancies, including 168 (9.3%) that developed PE. In the validation of the prior model based on maternal characteristics and medical history, calibration plots demonstrated very good agreement between the predicted risks and the observed incidence of PE (calibration slope and intercept for PE < 32 weeks were 0.827 and 0.009, respectively, and for PE < 37 weeks they were 0.942 and −0.207, respectively). In the combined data, there were 3938 pregnancies, including 339 (8.6%) that developed PE and 253 (6.4%) that delivered with PE at < 37 weeks' gestation. In twin pregnancies that delivered with PE, MAP, UtA‐PI and PlGF were, at earlier gestational ages, more discriminative than in singleton pregnancies and at later gestational ages they were less so. For PAPP‐A, there was little difference between PE and unaffected pregnancies. The best performance of screening for PE was achieved by a combination of maternal factors, MAP, UtA‐PI and PlGF. In screening by maternal factors alone, the DR, at a 10% false‐positive rate, was 30.6% for delivery with PE at < 32 weeks' gestation and this increased to 86.4% when screening by the combined test; the respective values for PE < 37 weeks were 24.9% and 41.1%. Conclusions: In the assessment of risk for PE in twin pregnancy, we can use the same prior model based on maternal characteristics and medical history as reported previously, but in the calculation of posterior risks it is necessary to use the new distributions of log10 MoM values of UtA‐PI, MAP and PlGF according to gestational age at delivery with PE. © 2020 International Society of Ultrasound in Obstetrics and Gynecology